Borderline - zaburzenie nietypowe czy niezrozumiałe? - Kuczyńska, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
In the paper the most important reasons which make BPD difficult to understand are indicated. Some suggestions how to overcome the existing difficulties in understanding BPD by means of both theoretical considerations and experimental work are also given. The paper deals with such problems as: - difficulties of BPDs definitions and their correct diagnosis, - multifactor etiology of BPDs and different forms of their treatments, - the fate of borderline patients - on the basis of Stone' (1992) research, - questions which need answers. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 238-258